2005
DOI: 10.1021/jm050891r
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent, Orally Available, and Isoform-Selective Retinoic Acid β2 Receptor Agonist

Abstract: 4'-Octyl-4-biphenylcarboxylic acid (1g, AC-55649) was identified as a highly isoform-selective agonist at the human RARbeta2 receptor in a functional intact cell-based screening assay. The subsequent hit to lead optimization transformed the lipophilic, poorly soluble hit into a more potent and orally available compound (2, AC-261066) with retained beta2 selectivity and greatly improved physiochemical properties. Being an isoform-selective RARbeta2 receptor agonist that discriminates between nuclear receptor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 12 publications
4
67
0
Order By: Relevance
“…To investigate the different effects of the individual RAR isoforms on CYP26 regulation in HepG2 cells, we used three selective RAR agonists: AM580 for RAR␣ (Delescluse et al, 1991), AC55649 for RAR␤ (Lund et al, 2005), and TTNPB as a pan-RAR agonist (Nagpal et al, 1995). Cells were treated for 24 h with the RAR agonists at a concentration of 10 nM, and cells were harvested at the end of this time period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the different effects of the individual RAR isoforms on CYP26 regulation in HepG2 cells, we used three selective RAR agonists: AM580 for RAR␣ (Delescluse et al, 1991), AC55649 for RAR␤ (Lund et al, 2005), and TTNPB as a pan-RAR agonist (Nagpal et al, 1995). Cells were treated for 24 h with the RAR agonists at a concentration of 10 nM, and cells were harvested at the end of this time period.…”
mentioning
confidence: 99%
“…Cells were treated for 24 h with the RAR agonists at a concentration of 10 nM, and cells were harvested at the end of this time period. For these agonists, a concentration of 10 nM has been shown to be selective for the target RARs, and the relevant RAR(s) have K d values less than 10 nM (Delescluse et al, 1991;Nagpal et al, 1995;Lund et al, 2005). The relative expression levels of the individual RAR isoforms, as indicated by mRNA levels, were quantified using real-time PCR in the HepG2 cells at baseline and after atRA treatment.…”
mentioning
confidence: 99%
“…We previously reported that AC261066, a highly selective agonist for RARβ2 (Lund et al, 2005), possesses glucose-lowering properties in dietary and genetic models of obesity and T2D (Trasino et al, 2016b;Trasino et al, 2016a). In this study we confirm those findings and now report that AC261 diminishes the severity of urine albumin excretion and improves a number of the structural and pathological hallmarks of DN (Brosius et al, 2009;Deji et al, 2009) in HFD-fed mice, including glomerular hypertrophy, mesangial expansion, GBM thickening, and podocyte effacement.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic Nephropathy Model: Wild type (Wt), 10-week old, male C57BL/6 mice fed a standard laboratory chow (13% kcal fat, #5053, Pico Diet, St. Louis, MO) were randomized to either: remain on a laboratory chow (control, n=4), or a high fat, diabetic nephropathy diet (HFD, n=8) (45% kcal fat, #58125, Test Diets, St. Louis, MO) for 16-weeks. Four weeks after beginning HFD treatment, HFD groups were further randomized to: i) remain on the HFD diet, plus drinking water containing 0.2% DMSO (HFD, n=4); or ii) the HFD diet, plus drinking water containing 3.0 mg/100 ml of AC261066 (AC261) [in 0.2% DMSO] (HFD+AC261, n=4), a highly selective, orally bioavailable RARβ2 agonist (Lund et al, 2005), for 12-weeks. At the end of the study, mice from all groups were subjected to intraperitoneal glucose tolerance testing (IPGTT) as previously described (Trasino et al, 2016b), spot urine analysis (Kurien and Scofield, 1999), and then mice were sacrificed for tissue harvesting and analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation